Blockade of PD-1, PD-L1, and TIM-3 Altered Distinct Immune- and Cancer-Related Signaling Pathways in the Transcriptome of Human Breast Cancer Explants - Reem Saleh (3513056) (2020)
Immune checkpoint inhibitors (ICIs) are yet to have a major advantage over conventional therapies, as only a fraction of patients benefit from the currently approved ICIs and their response rates remain low. We investigated the effects of different ICIs—anti-programmed cell death protein 1 (PD-1), anti-programmed death ligand-1 (PD-L1), and anti-T cell immunoglobulin and mucin-domain containing-3 (TIM-3)—on human primary breast cancer explant cultures using RNA-Seq. Transcriptomic data revealed that PD-1, PD-L1, and TIM-3 blockade follow unique mechanisms by upregulating or downregulating distinct pathways, but they collectively enhance immune responses and suppress cancer-related pathways to exert anti-tumorigenic effects. We also found that these ICIs upregulated the expression of other IC genes, suggesting that blocking one IC can upregulate alternative ICs, potentially giving rise to compensatory mechanisms by which tumor cells evade anti-tumor immunity. Overall, the transcriptomic data revealed some unique mechanisms of the action of monoclonal antibodies (mAbs) targeting PD-1, PD-L1, and TIM-3 in human breast cancer explants. However, further investigations and functional studies are warranted to validate these findings. Other Information Published in: Genes License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/genes11060703